Philosophy in the Islamic World in Context: Philosophy and Mysticism in the Islamic World - Hajatpour, Reza (De Gruyter, 2025)
In the quest for true knowledge, mysticism goes one step beyond philosophy. While philosophy and mysticism are considered two distinct disciplines with their own methodological approaches in the history of Islamic thought, their metaphysical concepts reveal significant points of intersection. Their convergence follows an inherent logic. In many Muslim circles, the methodological differences between the two are not regarded as an irreconcilable opposition. Philosophy seeks knowledge through rational reflection, whereas mysticism deepens these insights by experiencing them in a transcendent state of consciousness. The French orientalist Henry Corbin (d. 1978) argued that Islamic philosophy found its true purpose only after Averroes (Ibn Rushd) and especially with the Isfahan School and Ṣadr ad-Dīn Muḥammad Shīrāzī (known as Mullā Ṣadrā, d. 1640), within the tradition of “spiritual intellect” in Oriental wisdom. This school of thought is also referred to as “Oriental theosophy.” A central question in this context is whether this form of philosophizing, in Corbin’s sense, should be understood as a departure from rationalist tradition and a return to a spiritual mode of thinking, or whether, as Pierre Hadot (d. 2010) put it, philosophy is not merely a particular way of viewing the world but rather a way of life. In this understanding, philosophizing does not simply mean speculating, analyzing, or theorizing but rather leading a consciously reflective life. Whether Islamic philosophy adheres strictly to rational inquiry or transcends rationality to serve the mystical wisdom tradition ultimately depends on how philosophy is perceived within Islam and what role mysticism plays in this context. This edited volume examines the complex relationship between these two domains of human thought and way of life through concrete examples from the history of Islamic intellectual traditions. It not only elucidates the ways in which philosophy and mysticism are interconnected but also delineates the precise boundaries of their connection. The contributions in this volume explore both dimensions from various perspectives, highlighting their mutual influence and the intricate relationship between philosophy and mysticism